Inefficiency of Indian Real Estate indicators: A Need for Regulatory Agency & Index based on market deal - B, Muthupandian; Velmurugan (Journal of Management and Science, 2012)
The real estate sector is a major employment driver in India and it contributes a significant level to the GDP. Besides, it is the main source of wealth for all section of the people. There is no transparency and efficiency in the pricing of real estate transaction in-spite-of some indices representing the price movement of the real estate sector. This is because the price is based only on the primary market transaction. It‟s completely excluding the secondary market transaction of the sector. This paper attempts to address this issue by proposing an online exchange for real estate transaction, for bringing in more liquidity and transparency to the sector, along with an index, based on the price traded in that exchange. These will a high relative measure to indicate and represent the price moment of the sector. This kind of regular monitoring of the real estate prices may be fruitful input for the different stake holders like buyers, seller, mediators, developers, investors, banks, housing finance companies, FIIs, private equities, analysts and others in their decision-making process.